Evaluation of Revenue Accounting Implementation According to Government Regulation No. 71 Of 2010 in Regional Revenue Services of East Java Province - I Gusti Dimas Prasetyawan Ranuh; Heru Tjaraka (Return : Study of Management, Economic and Bussines, 2023)
This study was conducted to evaluate the application of revenue accounting in accordance with Government Regulation No. 71 Year 2010 on Government Accounting Standards on accrual basis in Regional Revenue Offices of East Java Province. The application of Government Accounting Standards on accrual basis have to be fully applied by the start of the year 2015. There is still many local government agencies that hasn’t fully applied government accounting standards on accrual basis, the reasons for local government agency that hasn’t fully applied government accounting standards is the lack of human resources that understand the government accounting standards on accrual basis in Government Offices, the accounting application systems that inadequate resulting in financial reporting took a long time. In This study, the writer has conducted interviews in Sub-Division of Finance, responsible to made the financial statements in Regional Revenue Offices of East Java Province. The Interviews conducted were about the application of Government Accounting Standards on accrual basis, revenue accounting policies. The results showed that Regional Revenue Offices of East Java Province has applied the Revenue Income appropriate with The Government Regulation No. 71 Year 2010 on Government Accounting Standards on accrual basis.